Protocolos de bioseguridad y su relación con la prevención de infecciones en pacientes quirúrgicos. Sala Magdalena. Hospital General Martín Icaza octubre 2024 – mayo 2025. - Elejama Cordonez, Laydi Carolina (2024)
Biosafety protocols in the health system are essential to generate favorable conditions for patients and health personnel; currently, there is a low rate of their application. The prevention of surgical infections is essential; however, the lack of training can contribute to the appearance of infections in surgical patients. The objective is to determine the relationship between biosafety protocols and infection prevention. The methodology applied according to the level of study was descriptive, according to the purpose, applied according to the place, field, cross-sectional and inductive-deductive method, the analysis and synthesis method. Patients from the Magdalena Ward with surgical procedures and the health personnel in charge of their care were included. The results show the predominance of patients aged 27 to 59 years (48%), undergoing gastrointestinal surgery (39%), emergency surgery (60%); surgical site infection was identified (40%), with 3 to 7 days of hospitalization, mild discomfort in the surgical wound (48%) and inflammation (36%). Regarding staff, there is a high level of compliance in the safe disposal of sharp objects (90%), they use personal protective equipment (88%), but most do not comply with hand washing (61%). It is concluded that the application of protocols has contributed to the reduction of the risk of infections, however, the low adherence to hand washing and the persistence of inflammatory signs suggest the influence of other factors.